Standardization of seed and seedling standards of phalsa (Grewia subinaequalis L.) (Indian Journal of Arid Horticulture, 2020)
Phalsa multiplication through seeds requires certain prerequisites i.e. fully ripened fruits and freshly extracted seeds for seedling raising, portrays for maximum seed germination per cent, germination more than 80% from fresh seeds and completed within 25 days after sowing with 60-90 per cent plant survival rate, during seedlings shifting in polybags require minimum 3-4 weeks period with height of about 4-5 cm, seedlings of about 3-4 months age group attaining height and diameter 35-40 and 0.25- 0.35 cm, respectively ready for sale or field planting. The developed standards would be highly useful for conservation of elite type germplasm and large scale multiplication of seedlings of phalsa.
Keywords: Phalsa; seed propagation; seed standards; seedling standards